Flow-level Load Balancing of HTTP Traffic using OpenFlow - Al-Najjar, Anees; Portmann, Marius; Layeghy, Siamak; Indulska, Jadwiga (Journal of Telecommunications and the Digital Economy, 2018)
In this paper, we explore the concept of flow-based load balancing of network traffic on multi-homed hosts. In contrast to existing approaches such as MultipathTCP, our approach is a client-side-only solution, and can therefore easily be deployed. We specifically explore flow-based load balancing for web and video traffic use cases. Experimental evaluations of our OpenFlow-based load balancer demonstrate the potential of flow-based load balancing.